First Report of Human Nasal Myiasis Caused by Eristalisin Iran (Diptera: Syrphidae)tenax - M Salimi; H Edalat; A Jourabchi; MA Oshaghi (Tehran University of Medical Sciences, 2010)
We report a case of human nasal myiasis caused by flower fly larva in a 14-year-old rural girl in Central Province of Iran. Entomological studies on larva showed the larva as Eristalis tenax which is a rarely cause of nasal myiasis. This is the first reported case of E. tenax larva causing human nasal myiasis in Iran.